Methane concentrations of sediment core GeoB16427-1 from the Japan Trench - Thomas Pape; Patrizia Geprägs; Martin Kölling; Gerhard Bohrmann; Gerold Wefer (PANGAEA, 2022)
Shallow sediment cores were collected with gravity cores from sites in the Japan Trench during cruise SO219A with R/V SONNE. In order to determine ex-situ concentrations of methane dissolved in pore water, sediment samples were taken from the sediment cores with cut-off syringes and transferred into glass vials. Methane concentrations in the headspace gas were used to calculate concentrations of methane dissolved in pore water (uncorrected for sediment porosity and Bunsen coefficient).